The Role of The Prosecutor as Executor of Court Decisions in Returning Confiscated Objects and State Spoils in Criminal Cases: Comparing Indonesia, Malaysia, Nigeria, and Thailan - Ameerah binti Amir; Wahyu Nur Hanifah; Anis Widyawati; Ngboawaji Daniel Nte; Arthur Smith (Indonesian Journal of Criminal Law Studies, 2022)
The execution of court decisions especially for confiscated objects and state spoils face some challenges in Indonesia. This research aims to find out the the executive of court decisions in the return of evidence, as well as what factors affect the presecutor as the executor of the court’s decision. The research questions formulated as first, what is the role of the presecutor in carrying out of the execution of the court's verdict on the return of evidence? and second, what are the factors that affect the presecutor as the executor of the court's decision in the return of evidence? The research method used in this research is qualitative research method with a type of socio-legal studies. This research found and highlighted that the execution of the court’s decision on the status of the evidence carried out by the Prosecutor after the adjudicator's decision has been signed. There are four factors that influence the level of effectiveness of the Prosecutor as the executor of court decisions with regard to evidence, including the legal factor itself, the community factor, the law enforcement officer factor, as well as the legal facilities and facilities factor. Various regulations have been drafted, however, none of them have explicitly regulated the threat of sanctions for prosecutors who do not immediately carry out executions, lack of coordination between related parties, and limited legal facilities and facilities are factors that affect the effectiveness of prosecutors in carrying out their duties.